Analysis of safe intervals for virtually coupled operation based on ETCS braking model - LI Qihe; LEI Chengjian; XIE Xing; CHEN Dong (机车电传动)
Instead of physical coupling, virtual coupling technology implements wireless communication and cooperative control between trains to create a virtual platoon of multiple trains operating under unified control. The operation of virtually coupled trains can shorten the distance between operating trains, increase traffic volumes of railways, and improve operational resilience without significant infrastructure renovations. Since the European Union designated virtual coupling as a key research topic in the Shift2Rail initiative, this technology has quickly become a research hotspot in the field of rail transit both domestically and internationally. In this context, ensuring the safety of trains operating at shorter intervals is recognized as a critical issue that must be addressed for the successful application of virtual coupling technology. The initial analysis identified the constituent elements for determining safe intervals between virtually coupled trains, based on the standard train braking model established for the European train control system (ETCS), leading to the development of a generic method for calculating these safe intervals. Subsequent simulating calculations analyzed the characteristics of safe intervals at various speeds, train models, and track slopes. Further study explored the impact of safe intervals on the application of virtual coupling technology on trunk railways, providing reference for implementing virtual coupling functionality in the upgrading of these railways.